Nesting records of Asian Woollyneck from Assam, Northeast India - Kakati, Ranjit; Borah, Dipankar; Sarma, Rahul; Mandal, Jaydev (Ecological Questions, 2022)
Asian Woollyneck Ciconia episcopus (Boddaert, 1786), is a Near Threatened species of stork restricted to South and South East Asia. Previously considered a seasonal migrant to the pains of Assam was found successfully breeding along the northern part of Kaziranga National Park in Assam. In this note, we provide observations of Asian Woollynecks nesting in three localities in Biswanath district with three successful and one unsuccessful attempt and four additional records from Majuli and Lakhimpur districts of Assam, India. So far, there were only two known breeding records of the species from Assam as well as the whole of Northeast India, hence our observation makes these records important for the conservation of the species in the whole region.